Activity based kinetics of CO2–OH− systems with Li+, Na+ and K+ counter ions. (12th September 2016) - Gondal, Shahla; Svendsen, Hallvard F.; Knuutila, Hanna K.
Abstract: In this work the applicability of activity based kinetics for the absorption of CO2 into hydroxide and carbonate solutions is discussed. It was found by several authors that reaction rate constants based on concentration strongly depend both on concentration and the counter ion present in solution. In this study experimental kinetics data for LiOH, NaOH and KOH from the literature were reevaluated using activity based kinetics. It is observed that the use of activities instead of concentrations eliminates the effect of both concentration and counter ion on the rate constant and an expression for the activity based second order rate constant is derived. The activities used in this work were calculated with the electrolyte-NRTL model which predicts well the equilibrium partial pressure of CO2, the composition of the liquid phase and the apparent Henry's law constant. The calculated activity coefficients were used to predict the activity based rate constant and CO2 flux from the concentration based second order kinetic constant at infinite dilution ( k OH − ∞ ). The infinite dilution rate constant, combined with e-NRTL based activities of CO2 and hydroxyl ion, predicted the CO2 absorption fluxes within 14% AARD showing that the proposed approach can be used for prediction of activity based rate constants and the CO2 absorption flux for any system involving the reaction of CO2 with hydroxyl ion. Highlights: Activities based kinetics for CO2 reaction with hydroxides of Li + Na + and K + are presented. An expression for the activity based second order rate constant is derived. The activities are calculated with the equilibrium model using electrolyte-NRTL model. The proposed method predicted the CO2 absorption fluxes within 14% AARD. It can predict activity based rate constants and CO2 flux for any CO2 –OH − system.